Lista Provisional de los peces de las aguas continentales de Costa Rica - Alpirez O., Olivier (Uniciencia, 1984)
A revised and amplified list of species of Costa Rican continental water fishes is presented. Some species are included for the first time in the Costa Rican freshwater ichthyofauna and others are not described yet to the species level. Some specimens of species mentioned here are deposited in the Museum of Zoology at the National University, Heredia, Costa Rica and others are in the Zoology Museum at the University of Costa Rica.